Resource planning methodology based on simulation in clothing production lines [Metodología basada en simulación para la programación de recursos en líneas de confección] (2018)
The resource planning problem in production lines is increasingly complex due to the continuous changes in market trends, so it is important to develop methodologies that allow companies to achieve production objectives at the lowest cost. In this article we present a methodology based on discrete event simulation in order to schedule resources in a clothing manufacturing plant of a large company. © 2018.